A Review of Silicon in Soils and Plants and Its Role in US Agriculture: History and Future Perspectives. Issue 9 (September 2016) - Tubana, Brenda S.; Babu, Tapasya; Datnoff, Lawrence E.
Abstract : Abstract: Silicon (Si) is the second most abundant element in the earth's crust and plays a number of important roles in the mineral nutrition of plants. In the past 20 years, the scientific documentation on the benefits of Si to crops has helped establish Si fertilization as an agronomic practice in many agricultural lands worldwide. However, very little information has been consolidated on the use of Si specifically for US agriculture. Consequently, the objectives of this review are to provide (1) information on the dynamics of Si in soil, use, and sources; (2) a history and up-to-date documentation on Si-related research in many areas of US production agriculture; and (3) perspectives on Si as a plant beneficial nutrient and the potential of Si fertilization as an agronomic practice in US crop production systems. The Si-driven mechanisms enhancing the productivity of a wide array of crops under stressed conditions are discussed in this review. Based on the recent 10-year average production level and published shoot Si content, the principal crops grown in the United States can collectively take up 9.55 million tons of Si annually, whereas the annual Si removal rate for the entire US cropland area is estimated at 21.1 million tons. On the basis of this projected annual Si removal rate, adoption of continuous intensive farming systems in the country, low solubility of soil Si, and complex chemical dynamics of Si in soil, increasing plant-available Si levels through fertilization is therefore foreseen a logical agronomic practice for US agriculture.